Research Progress on Probiotics in Alleviating Cow’s Milk Allergy: A Review - Yangze Guo; Jiali Chen; Yezhi Qu; Xilin Wu; Shengyi Zhang; Jiale Wang; Xiqing Yue; Zhenmin Liu; Aijun Xie; Mohan Li (Foods)
Cow’s milk allergy (CMA) is one of the most common food allergies in infancy, capable of triggering severe allergic reactions. Alterations in gut microbial composition and function may be closely related to the development of CMA. Probiotics, as a means to modulate the gut microbial composition, demonstrate potential in controlling allergic reactions by enhancing gut barrier functions, promoting immune responses in the intestinal mucosa, and degrading potential allergens. Therefore, probiotics are increasingly considered a promising strategy for managing CMA. This review summarizes the major allergens in cow’s milk, their mechanisms of allergenicity, and the role and mechanisms of probiotics in alleviating CMA. It aims to provide a deeper understanding and fresh perspectives to support the use of probiotics as an effective approach for the prevention and treatment of CMA, encouraging broader clinical application and research.